Factors of effect on the corrosion destruction of metal of underground pipelines - Polutrenko, M. S.; Fedorovych, Ya. T.; Dzudzylo, K. M. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
A set of studies was conducted to determine the main factors influencing the corrosion destruction of metal in underground pipelines in two studied sections of the Pasichna-Tysmenitsa gaspipeline, covering definitions of active acidity, mass fraction of moisture, the presence of sulfate ions, and metal weight loss determined by the gravimetric method. It has been established that the pipeline in the studied sections of the route is laid in a soil of uniform acidity, which is low in pH acidic, which indicates corrosiveness of the soil in relation to steel. High soil moisture from the bottom of the pipeline in two sections of the route 18.21 and 19.73 %, respectively, contributed to increased corrosion damage of the metal. Corrosion of the studied soils was carried out on the basis of certain metal weight loss. It was established that the soils on the studied sections of the route, the distance between which was about 1000 m, relate to soils with a high and normal degree of corrosivity. High corrosion activity is characteristic of the soil along the lower generatrix of the pipeline, which leads to an increase in the corrosion rate of the metal of underground pipelines in this zone. The intensification of corrosion processes in the soil adjacent to the pipeline, with an increase in metal exposure time in soil, has been established. The presence of sulfate ions in soil water extracts leads to the development of biocorrosion with the participation of sulfate-reducing bacteria, which indicated the formation of biogenic hydrogensulfide.